I hope this helps you
-x+4=2x+1
4-1=2x+x
3=3x
x=1
y=-1+4
y=3
The inverse of the function f(x) = 4(x-3)² + 2 is ![f^{-1}(x) = \sqrt{\frac{x-2}{4} } + 3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20%5Csqrt%7B%5Cfrac%7Bx-2%7D%7B4%7D%20%7D%20%2B%203)
The given function is:
f(x) = 4(x - 3)² + 2
To find the inverse of the function:
Make x as the subject of the formula
![4(x-3)^2 = f(x) - 2\\(x-3)^2 = \frac{f(x)-2}{4} \\x - 3 = \sqrt{\frac{f(x)-2}{4} } \\x = \sqrt{\frac{f(x)-2}{4} } + 3](https://tex.z-dn.net/?f=4%28x-3%29%5E2%20%3D%20f%28x%29%20-%202%5C%5C%28x-3%29%5E2%20%3D%20%5Cfrac%7Bf%28x%29-2%7D%7B4%7D%20%5C%5Cx%20-%203%20%3D%20%5Csqrt%7B%5Cfrac%7Bf%28x%29-2%7D%7B4%7D%20%7D%20%5C%5Cx%20%3D%20%5Csqrt%7B%5Cfrac%7Bf%28x%29-2%7D%7B4%7D%20%7D%20%2B%203)
Replace x by
and replace f(x) by x
![f^{-1}(x) = \sqrt{\frac{x-2}{4} } + 3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20%5Csqrt%7B%5Cfrac%7Bx-2%7D%7B4%7D%20%7D%20%2B%203)
Therefore, the inverse of the function is:
![f^{-1}(x) = \sqrt{\frac{x-2}{4} } + 3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20%5Csqrt%7B%5Cfrac%7Bx-2%7D%7B4%7D%20%7D%20%2B%203)
Learn more here: brainly.com/question/17285960
Answer:
50
Step-by-step explanation:
Figure out all variables
100/(2x5= 10)-9+(3x.33=1)
100/10-9+1
100/2
50